Update on the management of chronic myeloid leukemia: current best practice and future directions. (3rd April 2019) - Nee, Aisling; Lipton, Jeffrey H.
ABSTRACT: Introduction : Tyrosine kinase inhibitor (TKI) therapy has dramatically improved survival for patients with chronic myeloid leukemia (CML). The focus of CML therapy is now shifting to improvement in quality of life, reduction of toxicity, and economic burden. TKI therapy was once considered lifelong therapy; however studies in recent years have shown that cessation of TKI therapy without loss of molecular response, known as treatment-free remission (TFR), is achievable in a subset of CML patients. Another important development is the introduction of second- and third-generation TKIs of increased potency, each with a distinct toxicity profile but the potential to salvage patients with poor responses. Areas covered : Data on approved TKIs, including survival outcomes and toxicity profiles, are reviewed. TFR data and its application in clinical practice are discussed. Prevention and management of toxicities, with focus on long-term cardiovascular toxicity with TKIs, are also reviewed. Expert opinion : Choice of first-line TKI needs to be an individualized decision. Factors to consider include desired goal of care, patient comorbidities, and access to therapy. Patients should be educated on TKI toxicities and the potential for TFR. As second-generation TKIs are increasingly used, clinicians must be cognizant of their toxicities and proactive in prevention of adverse events.